Tracheal mites, Acarapis woodi, greatly increase overwinter mortality in colonies of the Japanese honeybee, Apis cerana japonica - Maeda, Taro; Sakamoto, Yoshiko (Apidologie, 2016)
This study evaluated the damage caused by the tracheal mite Acarapis woodi to colonies of the Japanese honeybee Apis cerana japonica , by investigating mite prevalence and colony death of the honeybees during winter. Honeybees of 114 colonies were sampled from October to December to detect mite prevalence. The colony death was monitored up to the end of April. The observed mortality due to mite infestation was compared with data from two previous studies about European honeybees. Under normal conditions in the absence of mites, 21 % of intact colonies died during the winter season. However, once the honeybee colonies were infested with A. woodi , the overwinter mortality was drastically increased. The mortality of Japanese honeybee colonies infested with the tracheal mites was higher than that reported historically in European honeybee colonies infested with the mites. Investigation of colony mortality at the apiary level showed that mortality was significantly higher in mite-infested than non-infested apiaries, but there were no significant differences related to the estimated winter air temperature. These results suggest that tracheal mite infestation seriously increases the overwinter mortality of Japanese honeybees.